Peran Public Relations dalam Manajemen Event (Studi Terhadap Peran Public Relations Galeria Mall dan Plaza Ambarrukmo dalam Pengelolaan Event Tahun 2013) - Mutia Dewi; Marcha Runyke (Jurnal Komunikasi, 2013)
Nowadays, Indonesian business are growing and developing rapidly. Every year, department store or mall are being build in many cities in Indonesian. This condition make every mall have to think about how to deal with the competition. Event are one program did by the mall’s management in order to attract customer. Event has to be well managed so that the event can give advantage for the mall. Event management is one of Public Relations (PR) department’s duty.This research discuss about Public Relations role in Galleria Mall PR Department and Plaza Ambarrukmo PR Department, related to event management. Both PR department do the writing media release, publicity, and media relations. Meanwhile there are difference role between Galeria Mall PR Department and Plaza Ambarrukmo PR Department in the role as conceptor, stage manager, and supporting unit.